2020
DOI: 10.1177/0961203320926253
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin kexin 9 is associated with disease activity and is implicated in immune activation in systemic lupus erythematosus

Abstract: Background Low-density lipoprotein (LDL) levels are increased by proprotein convertase subtilisin kexin 9 (PCSK9) which targets the LDL receptor. We recently reported that PCSK9 ameliorates dendritic cell (DC) activation by oxidized LDL (OxLDL), which is abundant in atherosclerotic plaques and is also associated with cardiovascular disease (CVD) in systemic lupus erythematosus (SLE). Here, we investigated the role of PCSK9 in SLE. Methods PCSK9 levels were determined by ELISA among SLE patients ( N = 109) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…Similarly to our findings, CRP was positively correlated with PCSK9 and patients on hydroxychloroquine had lower levels of PCSK9. 15 In another study, 16 PCSK9 levels were non-significantly different among SLE patients compared with controls but significantly associated with SLE disease activity, as determined by the SLEDAI. This study also lacked full lipid profiles assessment and multivariable adjustment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly to our findings, CRP was positively correlated with PCSK9 and patients on hydroxychloroquine had lower levels of PCSK9. 15 In another study, 16 PCSK9 levels were non-significantly different among SLE patients compared with controls but significantly associated with SLE disease activity, as determined by the SLEDAI. This study also lacked full lipid profiles assessment and multivariable adjustment.…”
Section: Discussionmentioning
confidence: 91%
“…Remarkably, PCSK9 levels were still downregulated in SLE patients after the multivariable analysis [beta coefficient -77 (95% CI -96 to −58) ng/ml, p ⩽ 0.001]. ACA IgM, n (%) 20 (10) ACA IgG, n (%) 31 (16) Anti beta2 glycoprotein IgM, n (%) 13 7Anti beta2 glycoprotein IgG, n (%) 22 (11) C3, mg/dl 96 ± 27 C4, mg/dl 17 ± 7…”
Section: Multivariable Analysis Of the Differences In Lipid Profiles mentioning
confidence: 99%
“…16 Earlier we have reported that PCSK9-levels are raised among patients with high disease activity in systemic lupus erythematosus (SLE), and that OxLDL induced PCSK9 in dendritic cells (DC), effects which were significantly stronger in DCs from SLE patients than from controls. 17 OxLDL, which is increased in SLE, induced PCSK9, an effect which was higher among SLE patients. We suggested that PCSK9 could play an imunological role in SLE.…”
Section: Introductionmentioning
confidence: 87%
“…We suggested that PCSK9 could play an imunological role in SLE. 17 Also other studies demonstrate pro-inflammatory effects of PCSK9. 15,18 We here report that low PCSK9-levels at start of anti-TNF treatment in patients with RA are associated with being a responder to that therapy and elucidate potential underlying mechanisms.…”
Section: Introductionmentioning
confidence: 93%
“…Earlier, we have reported that PCSK9-levels are raised among patients with high disease activity in systemic lupus erythematosus (SLE) and that OxLDL induced PCSK9 in dendritic cells (DC), effects which were significantly stronger in DCs from SLE patients than from controls [17]. OxLDL, which is increased in SLE, induced PCSK9, an effect which was higher among SLE patients.…”
Section: Introductionmentioning
confidence: 92%